Reception and risk classification in obstetric emergencies: a literature review (Research, Society and Development, 2021)
Obstetric emergencies are defined as situations that put the route of the pregnant woman and the fetus at risk, requiring immediate intervention by the health team in urgent and emergency units and delivery rooms. This is a quantitative bibliographic research, descriptive and exploratory, in electronic databases: LILACS, BVS and SCIELO. The bibliographic analysis corresponded to 7 articles eligible for the development of this study according to the inclusion and exclusion criteria, which correspond to 14.9% of the total available in the databases used as sources, 1 from the VHL, 2 from LILACS and 4 of SCIELO, where there is a predominance of published studies, considered resolute for the objectives, in the SCIELO database. The articles show that pregnancy is a period characterized by intense physiological changes in the female body. The gestational evolution can represent a risk factor for the occurrence of cases of maternal and neonatal morbidity and mortality, resulting from the so-called obstetric emergencies, which require immediate interventions by health professionals to minimize the vulnerabilities to which pregnant women may be exposed. that the nursing team plays a key role. Although the process of reception and classification of gestational risks requires differentiated attention and is essential to ensure greater survival and quality of care, it is observed that there is no specific sector and/or care for such situations, so that screening takes place in line with the other patients.